Silicon Photonic Biosensors for Lab-on-a-Chip Applications. (12th May 2008) - Zinoviev, Kirill; Carrascosa, Laura G.; Sánchez del Río, José; Sepúlveda, Borja; Domínguez, Carlos; Lechuga, Laura M.
Abstract : In the last two decades, we have witnessed a remarkable progress in the development of biosensor devices and their application in areas such as environmental monitoring, biotechnology, medical diagnostics, drug screening, food safety, and security, among others. The technology of optical biosensors has reached a high degree of maturity and several commercial products are on the market. But problems of stability, sensitivity, and size have prevented the general use of optical biosensors for real field applications. Integrated photonic biosensors based on silicon technology could solve such drawbacks, offering early diagnostic tools with better sensitivity, specificity, and reliability, which could improve the effectiveness of in-vivo and in-vitro diagnostics. Our last developments in silicon photonic biosensors will be showed, mainly related to the development of portable and highly sensitive integrated photonic sensing platforms.